The dialectical tradition in South Africa - Nash, Andrew (Department of Political Studies, 2023)
This study examines a specific current of political thought in South Africa, which is sometimes identified - in a way which obscures its character and development - as Afrikaner liberalism. This current of thought has as its core a defence of free speech in its classical, rather than modem liberal, sense as a precondition for a good society, rather than an individual right. The study traces this current from its sources in the uneven development of Western political thought in the 18th and 19th centuries, and through its development in South Africa from the mid-19th century to the present. I argue that this current of thought extends beyond Afrikaner political and intellectual life, that it is best interpreted as a tradition of dialectical thought, and that it represents the most distinctive and enduring form of dialectical thought in South Africa. In the aftermath ,0fthe American and French Revolutions, the central concepts in Western political thought were transformed, and in the process the classical republican idea of freedom - including freedom of speech - as the collective power of an active citizenry was displaced by the liberal idea of freedom as an individual right, which each could choose to exercise or not. By examining the ways in which the legacy of Socrates was re-interpreted in this time, and assimilated into liberal political thought, we can see how the dialectical capacities of that legacy came to be blunted in the process. In the Netherlands, however, the republican legacy of Socrates lived on, and a distinctive dialectical tradition emerged - especially within liberal Protestantism - which had considerable influence on intellectual life in the Cape Colony during the middle decades of the 19th century. The characteristic ideas and arguments of the dialectical tradition in South Africa emerged in the major intellectual conflict of that time - the so-called 'liberalism struggle' in the Dutch Reformed Church. Theological liberalism had been defeated by the 1870s, and its defeat cleared the way for a more conservative appropriation of the classical legacy - in which leading Cape liberals were prominent. But that legacy also served as a source for a dissenting view of history articulated by individuals of diverse political convictions - J.W.G. van Oordt, Olive Schreiner, Gandhi and others. This tradition found a more enduring institutional base in the academic discipline of philosophy at Stellenbosch, in the aftermath of the du Plessis case of 1928-32. The Stellenbosch philosophical tradition came to be transformed in the 1940s by a younger generation, largely through the assimilation of themes from Kierkegaard. Its themes were developed further in the work of Johan Degenaar, which led during the years of apartheid conformity to a vigorous critique of dogmatism and a dialectical account of the moral tasks of the individual. Sometime after 1970, however, as the apartheid regime began its attempts at pragmatic reform, this .tradition reached the limits of its call for oop gesprek. Central themes from this tradition were to be re-invented in the dialectical thought of Breyten Breytenbach, after the collapse of his venture into revolutionary politics in 1975, drawing on the dialectical capacities of Western Marxism, but seeking to deploy them in a more open-ended and dialogical way. Breytenbach's project had strong parallels with the work of Richard Turner, the major figure in the assimilation of Western Marxist ideas within the trade union and student movements in South Africa, which are also explored here. The most immediate context in which the future direction of this tradition is being decided is that of the new politics of Afrikaans, which has drawn on the legacy of Afrikaner opposition to apartheid and on Breytenbach's dialectical critique of the negotiated settlement in South Africa, but has at the same time failed to develop a collective alternative to the liberal capitalist model of freedom whose dominance threatens cultural and linguistic diversity